Toll 7 and Toll 9 in psoriasis vulgaris before and after phototherapy - Doaa Mahgoub; Amira M. El Tawdy; Mariam Makari; Laila Rashed (Our Dermatology Online, 2014)
Introduction: Psoriasis is a common chronic inflammatory, recurrent, immune mediated disease of the skin and joints. Toll-like receptors are pattern recognition receptors for conserved molecular patterns of pathogenic microorganisms.Under certain circumstances, self nucleic acids can trigger TLR 7 and TLR 9, which can lead to autoimmune diseases such as psoriasis. Materials and Methods: The study included 15 psoriatic patients (plaque type) and 15 controls, patients received 36 sessions of phototherapy (NB-UVB). Skin biopsies were taken from all the patients (before & after NB-UVB) and controls and were assessed for TLR 7 and TLR 9 by PCR. Results: Showed significant difference between patients and controls as regards TLR 7 and TLR 9. In addition a significant decrease in thier levels in patients after phototherapy with NB-UVB. Conclusion: TLR 7 and TLR 9 may play a role in the pathogenesis of poriasis. Decrease in their levels after NB-UVB may be one of the therapeutic mechanisms of NB-UVB in psoriasis.